Increased prevalence of epilepsy associated with severe falciparum malaria in children. - Carter, J; Neville, BG; White, S; Ross, A; Otieno, G; Mturi, N; Musumba, C; Newton, C (2004)
PURPOSE: Multiple, prolonged, generalized, or focal seizures are common in children with severe malaria, with or without coma. In other contexts, such seizures have been associated with the development of epilepsy. The relation between falciparum malaria and epilepsy is undetermined; thus we measured the prevalence and characteristics of epilepsy in children with a history of severe malaria. METHODS: We took a detailed epilepsy history from the parents of 487 children (aged 6-9 years) to compare the prevalence of epilepsy between three exposure groups: children with a history of cerebral malaria (CM), malaria and complicated seizures (M/S), or those unexposed to either complication. Each child had an EEG and was classified as having active, inactive, or no epilepsy. RESULTS: An increased prevalence of epilepsy was seen in children previously admitted with CM [9.2%; OR, 4.4; 95% confidence interval (CI), 1.4-13.7] or M/S (11.5%; OR, 6.1; 95% CI, 2.0-18.3) compared with the unexposed group (2.2%). The most commonly reported seizure types were tonic-clonic (42%), focal becoming secondarily generalized (16%), and both (21%). Twenty-six percent of the active epilepsy group initially had EEG abnormalities. CONCLUSIONS: These results suggest that children exposed to CM or M/S have an increased propensity for epilepsy relative to children unexposed to these complications. The prevalence of epilepsy associated with CM is similar to that reported after other severe encephalopathies. The prevalence associated with M/S is more than twice that reported after complicated febrile seizures.